Mitigating Hypoxic Stress in Juvenile Abalone (Haliotis squamata) through Optimized Carbohydrate Diets: Insights into Survival and Biochemical Adaptations - Dyahruri Sanjayasari; Wahyu Adi Septriono; Supono Supono; Amron Amron; Sesilia Rani Samudra; Mahardhika Nur Permatasari; Hery Irawan; Ainulyakin Hasan Imlani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Abalone (Haliotis squamata) is a high value marine mollusk with significant aquaculture potential in Indonesia. However, the production of this species faces major constraints, especially during the grow-out phase, due to high juvenile mortality during transport, primarily caused by hypoxic stress. This study investigated the effect of high carbohydrate diets on the physiological response and survival of juvenile abalone under simulated dry shipping-induced hypoxia. A total of 120 juveniles were fed five diets (Gracilaria sp. as a control, and formulated feeds with 25%, 35%, 45%, and 55% carbohydrate content) for 30 days prior the hypoxia treatment. The juveniles were then subjected to hypoxic conditions for 6, 12, and 24 h. All abalones survived the feeding period, but only individuals fed with 55% carbohydrate survived after 24 h of hypoxia. Abalones receiving 45% and 55% carbohydrate diets showed the highest protein and carbohydrate accumulation, respectively. Biochemical analysis revealed that hypoxia triggered a decrease in protein content, stable lipid levels, and fluctuating carbohydrate reserves. These results highlight the critical role of carbohydrates in supporting abalone under hypoxic stress and suggest that carbohydrate enriched diets could reduce mortality during dry transport and improve aquaculture outcomes.